Optimization of Pressurized Liquid Extraction of Carotenoids and Chlorophylls from Chlorella vulgaris - Cha, Kwang Hyun; Lee, Hee Ju; Koo, Song Yi; Song, Dae-Geun; Lee, Dong-Un; Pan, Cheol-Ho (AMER CHEMICAL SOC, 2010)
Pressurized liquid extraction (PLE) was applied to the extraction of carotenoids and chlorophylls from the green microalga Chlorella vulgaris. Four extraction techniques such as maceration (MAC), Soxhlet extraction (SOX), ultrasound assisted extraction (UAE), and PLE were compared, and both the extraction temperature (50, 105, and 160 degrees C) and the extraction time (8, 19, and 30 min), which are the two main factors for PILE, were optimized with a central composite design to obtain the highest extraction efficiency. The extraction solvent (90% ethanol/water) could adequately extract the functional components from C. vulgaris. PLE showed higher extraction efficiencies than MAC, SOX, and UAE. Temperature was the key parameter having the strongest influence on the extraction of carotenoids and chlorophylls from chlorella. In addition, high heat treatment (>110 degrees C) by PLE minimized the formation of pheophorbide a, a harmful chlorophyll derivative. These results indicate that PLE may be a useful extraction method for the simultaneous extraction of carotenoids and chlorophylls from C. vulgaris.
Keywords: ACCELERATED SOLVENT-EXTRACTION; SUPERCRITICAL CO2 EXTRACTION; DUNALIELLA-SALINA; FLUID EXTRACTION; PHEOPHYTIN; MICROALGAE; PHEOPHORBIDE; ANTIOXIDANTS; DERIVATIVES; ALGA